STRATEGI GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN ANAK SLOW LEARNER SAAT PEMBELAJARAN JARAK JAUH (pjj) DI SMP NEGERI 3 KRIAN SIDOARJO - Shoikhatul Jannah; Suryanto; Niken Titi Pratitis (JournEEL, 2021)
This study was conducted to describe the application of learning methods and media for slow learner children in order to improve the quality of slow learner children's learning during distance learning (PJJ). This research used qualitative research. Data collection techniques were observation, interviews and documentation studies. Data analysis techniques included data collection, data reduction, data presentation, drawing conclusions and verification. Based on the results of the analysis, the following results were obtained: (1) The subject teacher in making a learning plan did not differentiate between the slow learner and the regular child, but still paid attention to the characteristics of the slow learner. (2) in implementing the distance learning process remained the same as for normal children. Models, methods, learning media were the same, namely by using online media with the same time duration as normal children, but for slow learners there is an additional 2 hours of learning time for every two weeks through face-to-face learning activities ( Offline) and accompanied by a Special Assistance Teacher were carried out in schools with due observance of health protocols, (3) Evaluation of the slow learners (slow learner) was still carried out by subject teachers, the results of which were a reference for the follow-up activities of Special Assistance Teachers to provide guidance